Propuesta para la implementación de una Plataforma Virtual Educativa y mejorar la Formación Académica de los Aspirantes a Soldados de la ESFORSE. - Vergara Villarruel, Juan Francisco (2022)
A military educational institution requires high-quality processes in the training of students, training them professionally to face the new threats and risks that threaten the security of the State, however, in many cases time and physical space available are limited; and the cost of training is considerable. For this reason, the present study aims to carry out a comparative study, to identify the most appropriate virtual educational platform for implementation in ESFORSE together with its virtual model, which solves the educational needs of this institution. The methodology used is due to quantitative research that uses the survey as a means of data collection, and a qualitative one based on interviews, accompanied by a comparative analysis of secondary sources, the result of which shows that there is an improvement in the process of teaching-learning, with the implementation of education management systems for its acronym in English "LMS"; and reaffirms the interest of the institute to implement a platform together with a virtual model for the teaching-learning process of aspiring Army soldiers.